Investigating the Use of Mobile Assisted Language Learning (MALL) in University Students Context - Syafrizal (Journal of Education and Culture, 2024)
The aim of this study is to explore the students' perceptions in using the Mobile-Assisted Language Learning in university context. To collect the data, this survey research used online questionnaire adapted from Habiebie (2021), then analyzed descriptively. The participants of this study are 36 students from English Study Department of Islamic university of Indragiri. They are in second and fourth semester and selected using simple random sampling. The questionnaires were distributed using Google form. The result shows that 35.06% strongly agree, 47.88 agree, 13.01 neutral, only 1.88 disagree and 2.23 strongly disagree about the statements. It means most of the students have positive perception in using Mobile-Assisted Language Learning.